Building Democratic Values in Independent Policy Learning Through Multicultural Learning Communication - Ngalimun Ngalimun; Abdul Matin; Muhammad Munadi (Transformatif, 2022)
The objectives of multicultural-based education can be identified: (1) to function the role of schools in viewing the existence of diverse students; (2) to assist students in developing positive treatment of differences in cultural, racial, ethnic, religious groups; (3) providing resilience to students by teaching them to make decisions and social skills; (4) to assist students in building cross-cultural dependencies and give them a positive picture of group differences. In addition, multicultural-based learning is built on the concept of education for freedom which aims to: (1) help students or students develop knowledge, attitudes and skills to participate in democracy and community freedom; (2) promote freedom, skills, skills across ethnic and cultural boundaries to participate in some groups and other cultures.